Evaluation of the Effects of Cultivar and Location on the Interaction of Lentil Seed Characteristics with Optimal Cooking Time - Dimitrios Sarakatsianos; Dimitra Polyzou; Athanasios Mavromatis; Dimitrios N. Vlachostergios; Dimitrios Gerasopoulos (Seeds)
The most important product of the lentil crop (Lens culinaris Medik) is the seeds. The main seed characteristics are their size, color, and the cooking time required to make them edible. Cultivar, location of cultivation, and their interaction are the primary factors of raw or cooked seed characteristics. The study examined the impact of five different lentil cultivars (Dimitra, Elpida, Thessalia, Samos, and 03-24L), as influenced by the cultivation environment in four different zones or nine different locations in Central-Northern Greece, on cooking time. The optimal cooking time (OCT) was calculated by cooking the seeds for 0–60 min to determine the percentage of cooked seeds using the penetration test. OCT was associated with the characteristics of both raw (mass of 1000 seeds, external color, and the percentage of mature/immature seeds) and cooked (color and organoleptic characteristics of the cooking media as well as mass increase and hardness and organoleptic characteristics of the seeds) seeds for 30 min. Depending on location, each cultivar had a different mass of 1000 seeds; Elpida had the highest mass (63.9 g), and Dimitra had the lowest (33.1 g). This was linked to OCT, which was among the highest (57.5 min) for Elpida, lowest (49 min) for Dimitra, and intermediate for Thessalia, Samos, or 03-24L. The average OCT was 55.9 min for all samples. The seed from the five locations with the shortest OCT was considered appropriate for human consumption. Two locations yielded seeds with intermediate OCT, while the other two produced the highest OCT; these were recommended for processing or propagation. In this study, the cultivar factor had a greater effect on raw seed characteristics, while the location factor had a greater effect on cooked seed characteristics and OCT than either the location, the cultivar factor, or the cultivar x location interaction.